1986
DOI: 10.1136/thx.41.7.552
|View full text |Cite
|
Sign up to set email alerts
|

Influence of circulating alpha adrenoceptor agonists on lung function in patients with exercise induced asthma and healthy subjects.

Abstract: The influence of circulating noradrenaline (in this context primarily a non-selective ai agonist) and the a, selective agonist phenylephrine on bronchial tone, blood pressure, and heart rate was studied in eight patients with exercise induced asthma and eight age and sex matched controls. All subjects refrained from taking treatment for at least one week before the trial. The agonists were infused intravenously in stepwise increasing doses of 0.04, 0.085, 0.17, and 0.34 Mg/kg a minute for noradrenaline and 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Since circulating noradrenaline does not influence bronchial tone or reactivity [19,20), the effects of circulating catecholamines on the airways are caused by adrenaline. There is no circadian variation in the response to B-adrenoceptor stimulation [21], but it has been found that the morning-dip in lung function c oincides with trough values in plasma adrenaline levels and a causal connection between these two phenomena has been proposed [2,3).…”
Section: Discussionmentioning
confidence: 99%
“…Since circulating noradrenaline does not influence bronchial tone or reactivity [19,20), the effects of circulating catecholamines on the airways are caused by adrenaline. There is no circadian variation in the response to B-adrenoceptor stimulation [21], but it has been found that the morning-dip in lung function c oincides with trough values in plasma adrenaline levels and a causal connection between these two phenomena has been proposed [2,3).…”
Section: Discussionmentioning
confidence: 99%